Ethical dimensions in nursing care for individuals with intellectual disabilities - Elmadani, Mohammed (Nursing ethics, 2026)
Background Individuals with intellectual and developmental disabilities (IDD) face significant health disparities, often exacerbated by ethical and legal complexities in nursing care. Nurses are frequently challenged to balance autonomy, informed consent, patient safety, and human rights, especially in settings with unclear guidelines or insufficient training. This narrative review explores the ethical and legal considerations in nursing care for individuals with IDD, aiming to highlight challenges and propose best practices.Methods A narrative review methodology was employed to synthesise evidence from qualitative, quantitative, mixed-methods studies, theoretical articles, and grey literature. A comprehensive search was conducted across PubMed, EBSCO, Embase, Scopus, and Web of Science, using keywords related to ethical issues, legal rights, nursing, and intellectual disability. Studies were included if they addressed the ethical or legal dimensions of nursing care for people with IDD. Data were synthesised narratively and visually mapped using conceptual mapping techniques. Quality was assessed using the SANRA scale.Results Eighteen studies met the inclusion criteria. The findings reveal ethical tensions in obtaining informed consent, maintaining autonomy, and ensuring dignity against communication barriers and behavioural challenges. Nurses reported experiencing an emotional burden and ethical uncertainty when institutional constraints limit person-centred care. The overuse of restrictive practices and limited access to tailored healthcare were recurrent concerns. Legal challenges included complexities in guardianship, consent to treatment, and discriminatory practices. Emerging issues, such as the ethical use of artificial intelligence in care planning, were also noted.Conclusion Nursing care for individuals with IDD requires ethically grounded, legally informed, and person-centred approaches. Best practices include accessible communication, interdisciplinary collaboration, tailored education, and advocacy. Nurses must receive support through training and organisational frameworks to navigate complex ethical decisions and uphold the dignity and rights of individuals with IDD. These findings have direct implications for nursing practice and policy, offering actionable guidance to improve ethical decision-making, communication, and inclusive care delivery for individuals with intellectual disabilities.